2021
DOI: 10.1186/s41043-021-00225-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with self-efficacy in patients with hypertension: a cross-sectional study from Palestine

Abstract: Background Self-efficacy is a widely applied psychosocial concept that is commonly used in association with management of chronic diseases, including hypertension. The aim of this study was to assess self-efficacy of hypertension management and patient-physician communication, as well as the factors associated with self-efficacy and patient-physician communication among patients with hypertension in Palestine. Methods We conducted face-to-face, que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 24 publications
0
7
1
Order By: Relevance
“…Suksatan 22 also found that the perceived benefits of adopting HPBs influenced the HPBs of people at risk of hypertension in a rural Thai community (β = 0.402; p < 0.001). Additionally, perceived self-efficacy is a significant factor influencing HPBs and can predict the health outcomes of hospitalization and the quality of life of patients with NCDs (eg, diabetes, 32 hypertension, 33 heart failure, 34 and COPD 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Suksatan 22 also found that the perceived benefits of adopting HPBs influenced the HPBs of people at risk of hypertension in a rural Thai community (β = 0.402; p < 0.001). Additionally, perceived self-efficacy is a significant factor influencing HPBs and can predict the health outcomes of hospitalization and the quality of life of patients with NCDs (eg, diabetes, 32 hypertension, 33 heart failure, 34 and COPD 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…The multiple regression results are shown in Table S2 of Supporting Information. The indicator “ t stat” is the testing statistic of the t -test, whose absolute value can be used as the basis for judging the order of importance of factors . It can be clearly seen from Table S2 that the importance of factors is in the order of hydrocalumite > tobermorite > analcime > others > katoite.…”
Section: Resultsmentioning
confidence: 99%
“…The indicator "t stat" is the testing statistic of the t-test, whose absolute value can be used as the basis for judging the order of importance of factors. 65 It can be clearly seen from Table S2 that the importance of factors is in the order of hydrocalumite > tobermorite > analcime > others > katoite. For the removal percentage of total concentration of PAHs, the same result was observed (as shown in Table S3 of Supporting Information).…”
Section: Methodsmentioning
confidence: 97%
“…Snack foods intake has recently been emphasized as a potentially unhealthy eating habit [ 6 ]. Intake of energy-dense nutrient poor snacks from 1 serving per day to ≥ 2 serving per week, which are high in simple sugars, sodium, saturated and trans fatty acids, impose individuals to a higher risk of CVD and MetS [ 7 ]. Additionally, a 20% increase in the frequency of snacks intake was associated with weight gain and dysglycemia [ 8 ], and metabolically unhealthy obese subjects had a higher frequency of salty snacks, compared with metabolically healthy obese subjects [ 9 ].…”
Section: Introductionmentioning
confidence: 99%